Terapi bekam basah area punggung mengurangi nyeri sendi pada pasien rheumathoid arhtritis - Pringgayuda, Fitra; Idayati, I; Indiaresti, Purwati (Wellness And Healthy Magazine, 2020)
Rheumatoid Arthritis (RA) is a chronic systemic inflammatory disease of unknown cause with peripheral joint manifestations. The numbers of Genesis Rheumatoid Arthritis in Indonesia is quite high. RA Pain prevalence in Indonesia reached 25.6% to 35.8%. This figure suggests that pain due to RA already bothersome activity of Indonesia society. The aim of this research is conducted to know the effect find of wet cupping therapy in the area of paint in the back joint to changes in outpatient RA patients in clinics of the year 2018. A quasi-experimental design with One Group Pretestpostest Design without control. The population in this research is the sufferer Rheumatoid Arthritis 30-50 years old visiting Clinics Sukoharjo, with a sample of 16 respondents, purposive Sampling techniques. Wilcoxon test result indicates that there is a difference between pain before with after bekam, based on the result of the statistical test p-value obtained value is a ρ=0,001 (less than 0,05), this means there is a significant influence of wet cupping therapy to changes pain in people with Rheumtaoid Arthitis. Thus, wet cupping therapy can be a solution to reduce joint pain for patients with Rheumatoid Arthritis.